Resolving Information Asymmetry: Signaling, Endorsement, and Crowdfunding Success. (29th December 2016) - Courtney, Christopher; Dutta, Supradeep; Li, Yong
Abstract : This article draws on information economics to examine when signals and endorsements obtained from multiple information sources enhance or diminish one another's effects. We propose that signals through start‐up actions (use of media) and characteristics (crowdfunding experience) can mitigate information asymmetry concerns about project quality and founder credibility, enhancing the project's likelihood of attaining funding. Further, we posit that while start‐up–originated signals offset each other's effects, third‐party endorsements (sentiment expressed in backer comments) validate and complement start‐up–originated signals. Empirical analyses based on a comprehensive dataset of crowdfunding projects on the Kickstarter website during 2009–2015 confirm our predictions.